Effects of topical medications on radial artery spasm in patients undergoing transradial coronary procedures: a systematic review protocol. (October 2016) - Curtis, Elizabeth; Fernandez, Ritin; Lee, Astin
Abstract : Review objective: The objective is to identify the effectiveness of topical medications in reducing radial artery spasm in patients undergoing transradial coronary procedures.